2009
DOI: 10.1158/1535-7163.mct-09-0549
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide is an inhibitor of RNA polymerase I and II–dependent transcription leading predominantly to down-regulation of short-lived mRNA

Abstract: Triptolide, a natural product extracted from the Chinese plant Tripterygium wilfordii, possesses antitumor properties. Despite numerous reports showing the proapoptotic capacity and the inhibition of NF-κB-mediated transcription by triptolide, the identity of its cellular target is still unknown. To clarify its mechanism of action, we further investigated the effect of triptolide on RNA synthesis in the human non-small cell lung cancer cell line A549. Triptolide inhibited both total RNA and mRNA de novo synthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 46 publications
10
139
0
Order By: Relevance
“…3C) cells to 300 nmol/L CX-5461 (that resulted in 63% and 55% reductions in pre-rRNA, respectively), an equal number of Pol II-transcribed genes were significantly upregulated as were downregulated. These changes in Pol II transcription were most likely secondary to the inhibition of Pol I by CX-5461, as an inhibition of Pol II transcription results in a distribution significantly skewed to the negative (16). To further illustrate selectivity of CX-5461 for Pol I versus Pol II transcription, we compared it with another drug (actinomycin D) known to inhibit Pol I transcription.…”
Section: Biological Characterization Of Cx-5461mentioning
confidence: 99%
“…3C) cells to 300 nmol/L CX-5461 (that resulted in 63% and 55% reductions in pre-rRNA, respectively), an equal number of Pol II-transcribed genes were significantly upregulated as were downregulated. These changes in Pol II transcription were most likely secondary to the inhibition of Pol I by CX-5461, as an inhibition of Pol II transcription results in a distribution significantly skewed to the negative (16). To further illustrate selectivity of CX-5461 for Pol I versus Pol II transcription, we compared it with another drug (actinomycin D) known to inhibit Pol I transcription.…”
Section: Biological Characterization Of Cx-5461mentioning
confidence: 99%
“…Triptolide possesses multiple apparently unrelated activities, including anti-inflammatory, immunosuppressive, antifertility, anticystogenesis, and anticancer activities (1), which seem to suggest multiple molecular mechanisms involved in those activities. Moreover, according to a comparative analysis using the NCI-60 internal database, the GI 50 profile of triptolide is significantly different from those of 118 reference anticancer compounds (2), suggesting that triptolide could have anticancer mechanisms and molecular targets potentially distinct from those of other anticancer agents. Consistent with its various activities, triptolide has been revealed to interact with several cellular proteins, including polycystin-2 (PC-2), disintegrin and metalloprotease 10 (ADAM10), dCTP pyrophosphatase 1 (DCTPP1), and XPB (1).…”
Section: Introductionmentioning
confidence: 99%
“…Triptolide inhibits RNA polymerase II (RNAPII)-dependent transcription, showing a distinct mode of action from those of other known transcriptional inhibitors, including 5,6-dichloro-1-b-D-ribofuranosylbenz-imidazole (DRB) and flavopiridol (CDK9 inhibitors), actinomycin D (a DNA binder), and a-amanitin (an RNAPII inhibitor; refs. [2][3][4][5]. Triptolide is thus considered to be a new type of transcriptional inhibitors (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In endometrial and ovarian cancer cells, triptolide has been reported to have the anti-growth activity via targeting some specific genes, such as LRAP, CDH4, SFRP1 and so on . Besides, some studies indicate that triptolide could act as the inhibitor of RNA polymerase I and II-dependent transcription promoting some short-lived mRNA, for example cell cycle regulator CDC25A (Vispé et al, 2009). Celastrol is another main component isolated from radix tripterygii wilfordii, which has been reported to have the anti-cancer effect in cancer cell lines including leukemia , glioma ) and so on.…”
Section: Radix Tripterygii Wilfordii (Lei Gongteng In Chinese)mentioning
confidence: 99%